The potential influence of hyperthyroidism on circulating adipokines chemerin, visfatin, and omentin - Alshaikh, Eman M.; Omar, Ulfat M.; Alsufiani, Hadeil M.; Mansouri, Rasha A.; Tarbiah, Nesrin I.; Alshaikh, Abdelrhman A.; Rahimulddin, Sawsan A.; Al Doghaither, Huda A. (International Journal of Health Sciences, 2019)
Objectives: The aim of this study was to investigate the potential influence of hyperthyroidism on serum chemerin, visfatin, and omentin concentrations. The relationship between these adipokines and thyroid profile values was also investigated. Methods: A total of 140 female Saudi participants aged 20–45 years were recruited and divided into two groups, the euthyroid control group (n = 70) and the hyperthyroidism group (n = 70). Chemerin, visfatin, omentin, and thyroid profile including thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), total triiodothyronine (TT3), total thyroxine (TT4), and thyroglobulin were measured for all participants. Results: Serum chemerin levels were significantly higher in patients with hyperthyroidism compared to the controls. In contrast, serum visfatin and omentin concentrations were significantly lower in hyperthyroid patients than controls. Moreover, serum chemerin concentrations were positively correlated with TT3, TT4, and FT3 and negatively correlated with TSH and FT4. A negative correlation was also found between FT4 and TT4 and serum visfatin concentrations. Inversely, TSH correlated positively with serum visfatin levels. No significant correlation was observed between serum omentin concentrations and any of the thyroid profile variables except FT3. Conclusion: Hyperthyroidism influences serum chemerin, visfatin, and omentin concentrations, and these adipokines are correlated with thyroid hormones.